2022
DOI: 10.3390/pr10061222
|View full text |Cite
|
Sign up to set email alerts
|

From Foods to Chemotherapeutics: The Antioxidant Potential of Dietary Phytochemicals

Abstract: Food plants have been recognized for their medicinal properties for millennia, a concept supported by epidemiological studies indicating long-term health benefits for people consuming greater amounts of fruits and vegetables. As our technology and instrumentation advance, researchers have the ability to identify promising phytochemicals, and examine their potential benefits, or detriments, to human health. While results from trials investigating single chemical supplementation have sometimes produced negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 208 publications
(238 reference statements)
0
3
0
Order By: Relevance
“…The antioxidant capacity of plasma is associated with antioxidant food consumption [174]. Consuming an antioxidant-rich diet is believed to help prevent the negative effects of aging and behavior [175]. It was suggested that the consumption of polyphenolics present in fruits and vegetables could be effective anti-aging agents [176].…”
Section: Anti-agingmentioning
confidence: 99%
“…The antioxidant capacity of plasma is associated with antioxidant food consumption [174]. Consuming an antioxidant-rich diet is believed to help prevent the negative effects of aging and behavior [175]. It was suggested that the consumption of polyphenolics present in fruits and vegetables could be effective anti-aging agents [176].…”
Section: Anti-agingmentioning
confidence: 99%
“…Additionally, these substances have been extracted from fruit and plant medicines [59] . Alternative medicine and dietary approaches are inducing cell arrest and apoptosis, and increasing the sensitivity of cancer cells to radiation and chemotherapy [60] .…”
Section: Chemoprevention Perspectives Of Dietary Foodsmentioning
confidence: 99%
“…In addition, exogenous antioxidants provided through the diet may help protect the body from oxidative stress and associated health problems [10]. Well-studied examples are phenolic compounds such as phenolic acids, flavonoids, anthocyanins, and tannins [11] along with vitamins such as ascorbic acid and α-tocopherol, β-carotene, polyunsaturated fatty acids, and essential minerals such as selenium [12]. These substances prevent the formation of ROS or interrupt their propagation, scavenge ROS, remove intermediates of ROS in redox reactions, inhibit ROS-generating oxidation reactions, and repair oxidized molecules [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%